Double-layer carotenoid-rich emulsions as fat replacers: Application in salad dressings and low-fat chocolate cakes. - Silva Santos, Jhonatan [UNESP]; Freitas Ribeiro, Mírian Luisa Faria [UNESP]; Nicoletti, Vânia Regina [UNESP] (SAGE Publications, 2025)
The growing consumption of salad dressings has driven the use of emulsion technology to develop foods with low oil content while maintaining high nutritional value. This study aimed to formulate emulsions using buriti (Mauritia flexuosa) and sunflower oils, stabilized by a double-layer system of soy protein and high-methoxyl pectin. These emulsions, rich in carotenoids and low in fat, were applied to low-fat salad dressings and as fat substitutes in chocolate cakes. Composition results showed carotenoid concentrations of up to 76.44 μg/g in salad dressings and 253.55 μg/g in vegetable creams. Both products exhibited pseudoplastic rheological behavior with weak gel viscoelastic properties. Variations in the buriti oil-to-sunflower oil ratio did not affect the rheological properties of the creams, but increasing total oil content increased their consistency index, whereas the creams with 50% oil displayed viscoelastic behavior. Cakes made with fat substitutes were firmer than those made with oil and had increased adhesiveness due to higher water content. Overall, the results demonstrated that it is possible to reduce calorie content and enhance vitamin levels without significantly altering the texture parameters of cakes or the rheological properties of dressings, meeting the market demand for low-fat products.